Head, Neck, and Abdominopelvic Septic Thrombophlebitis: Current Evidence and Challenges in Diagnosis and Treatment - Valerio, Luca; Riva, Nicoletta (Hämostaseologie, 2020)
Septic thrombophlebitis (STP) is a complex, cross-disciplinary clinical condition that combines a localized infection with a neighboring venous thrombosis. STP can occur at several possible anatomic sites, such as dural sinuses, jugular vein (Lemierre syndrome), portal vein (pylephlebitis), and pelvic veins. Its high mortality in the preantibiotic era improved considerably with the introduction of modern antibiotics. However, little evidence exists to date to guide its clinical management. The incidence of STP or its risk factors may be increasing, and its mortality may still be considerable. These trends would have far-reaching implications, especially in the setting of increasing resistance to antimicrobial agents. No clinical assessment tools exist to support patient screening or guide treatment in STP. Few interventional studies exist on the efficacy and safety of anticoagulation. Recommendations on its indications, duration, and the agents of choice are mostly based on evidence derived from small observational studies. While all forms of STP pose similar challenges, future research may benefit from the distinction between bacteria-associated, virus-associated, and mycosis-associated thrombophlebitis. Addressing these gaps in evidence would enhance our ability to diagnose this condition and treat patients effectively.
Keywords: septic thrombophlebitis; venous thromboembolism; Lemierre syndrome; pylephlebitis; bacterial infection; anticoagulant